2021
DOI: 10.3390/ijms22063196
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas Technology in Pig-to-Human Xenotransplantation Research

Abstract: CRISPR/Cas (clustered regularly interspaced short palindromic repeats linked to Cas nuclease) technology has revolutionized many aspects of genetic engineering research. Thanks to it, it became possible to study the functions and mechanisms of biology with greater precision, as well as to obtain genetically modified organisms, both prokaryotic and eukaryotic. The changes introduced by the CRISPR/Cas system are based on the repair paths of the single or double strand DNA breaks that cause insertions, deletions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 164 publications
0
32
0
Order By: Relevance
“…However, xenogeneic transplantation from pigs to humans is compromised by high immune incompatibility and a complex rejection process. However, the rapid development of genetic engineering techniques enables genome modifications in pigs that reduce the cross-species immune barrier (Ryczek et al 2021 ). Xenotransplantation is a multidisciplinary undertaking, requiring the development of a range of research methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, xenogeneic transplantation from pigs to humans is compromised by high immune incompatibility and a complex rejection process. However, the rapid development of genetic engineering techniques enables genome modifications in pigs that reduce the cross-species immune barrier (Ryczek et al 2021 ). Xenotransplantation is a multidisciplinary undertaking, requiring the development of a range of research methods.…”
Section: Discussionmentioning
confidence: 99%
“…Gene editing combined with SCNT has been achieved in both species (Liu et al, 2018b;Yan et al, 2018;Zhou et al, 2015). The advantage of SCNT is that the animals produced by this technology are consistent without mosaics (Ryczek et al, 2021). For large animals, Figure 2 Animal models produced by different methods.…”
Section: Somatic Cell Nuclear Transfermentioning
confidence: 99%
“…They found that the mouse had decreased plasma levels of PCSK9. (Butler et al, 2016;Fischer et al, 2020;Fu et al, 2020;Ladowski et al, 2019;Ryczek et al, 2021). In the future, the "ideal" modified pig could be produced with advanced geneediting technology for the benefit of patients.…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Thus, there are numerous genetically‐modified pig models currently available in xenotransplantation research each with their own demonstrated benefits. For a comprehensive review of these models, we direct readers to recently published reviews in the field 23,45 …”
Section: Immune Rejection Of Xenograftsmentioning
confidence: 99%